(untitled) (SAARC Journal of Agriculture, 2026)
Jute is the cornerstone of Bangladesh’s fiber sector and makes a substantial contribution to the economy. This study sought to evaluate the profitability and value-added activities of various stakeholders in jute production and marketing, along with the challenges. The present study purposively selected the Madaripur and Faridpur districts. This investigation included 148 randomly selected samples, 120 of which were collected from farmers in two districts, with 60 samples from each district. The remaining 28 samples consisted of 11 faria, 14 mahajon and three processors. The study revealed that jute production yielded an average of 2,103 kg/ha, generating a gross return of Tk. 173,146, with a total cost of Tk. 105,624, resulting in a net return of Tk. 67,522 and the benefit‒cost ratio (BCR) was 1.64, significantly enhancing farm profitability. Econometric analyses, including a logit model, were employed to identify the key determinants of jute cultivation. The results revealed that age, family size, training, credit, and more profitable than competitive crops significantly influenced the willingness/adoption of jute cultivation (p<0.05), whereas education and annual income had negative effects. The study revealed that farmers gained the highest value addition at Tk. 20.37/kg (37.14% return on cost) compared with faria (Tk. 2.10/kg; 1.48%), and mahajon (Tk. 2.78/kg; 1.55%). The key challenges in jute production are high seed prices (73%), labor shortages (76%), and high wages (78%), whereas traders and processors face severe financial and supply uncertainties (73-100%), which limit productivity and profitability. SAARC J. Agric., 23(2): 217-238 (2025)